Aligning means and goals: Insights from professional development to promote learner-centered education in Cambodia - Eastman, Dennis (International journal of Christianity & education, 2023)
As part of a multi-year project within a network of Cambodian Christian schools, researchers facilitated training with the purpose of strengthening learner-centered education. To support teachers to grow beyond previous training, leaders ensured that the structure of the training was carefully aligned with intended outcomes. Informed by questionnaires that measured teacher confidence with varied tasks, and also by teacher feedback, researchers found evidence that it was helpful that the training was delivered in a manner consistent with principles of servant leadership and that it actually modeled learner-centered education so that teachers could integrate new pedagogies into their own classroom.